The Influence of Competence and Professional Skepticism on Auditor Performance: Self-Efficacy as a Mediator and Spiritual Quotient (SQ) as a Moderator - Abdi Bhayangkara; Ratnawati, Vince; Hardi (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study examines the relationships between competence, professional skepticism, and self-efficacy as a mediator of auditor performance, with the moderating role of Spiritual Quotient (SQ). Conducted at the Inspectorate of the Provincial Government of Riau with 106 auditors, the research utilized Structural Equation Modeling (SEM) via Smart PLS 4 for data analysis. The findings reveal that self-efficacy mediates the relationship between competence and skepticism on auditor performance, while SQ moderates the link between competence and performance. This study deepens understanding of the dynamics affecting auditor performance, highlighting the critical roles of self-efficacy and SQ. The results offer significant theoretical and practical implications for auditing, providing a foundation for future research.